2017
DOI: 10.1017/s0021859617000491
|View full text |Cite
|
Sign up to set email alerts
|

Validation of analytical method and evaluation of clothianidin residues in rice in a typical Chinese field ecosystem

Abstract: SUMMARYA liquid chromatography mass spectrometry method for determination of clothianidin in brown rice, straw, rice hull, paddy water and paddy sediment was developed and residue levels were determined in the different components. The limit of quantification was set at 0·01 mg/kg for the matrices studied. Clothianidin degradation in straw, paddy water and soil was studied, and clothianidin residues in brown rice, straw, hull and paddy soil were determined. Concurrent recoveries were between 85·6 and 92·5%, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since their inception in the 1990s, systemic pesticides, such as neonicotinoid insecticides (neonics) and triazole fungicides, have been widely used in seed treatment applications for the purpose of combating pest problems from below ground insects and soil borne microbials. Although systemic pesticides were known to have short biological half-lives, recent studies have demonstrated that they could be retained in groundwater and soil over a long period of time before eventually being degraded. Therefore, the ubiquity of systemic pesticides in the soil environment is expected in the combination of the repetitive sowing of treated seeds and their extended half-lives in soil. The persistence of systemic pesticides in soil would subsequently render unintended ecological hazards to those nontarget but essential organisms in soil and watersheds. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their inception in the 1990s, systemic pesticides, such as neonicotinoid insecticides (neonics) and triazole fungicides, have been widely used in seed treatment applications for the purpose of combating pest problems from below ground insects and soil borne microbials. Although systemic pesticides were known to have short biological half-lives, recent studies have demonstrated that they could be retained in groundwater and soil over a long period of time before eventually being degraded. Therefore, the ubiquity of systemic pesticides in the soil environment is expected in the combination of the repetitive sowing of treated seeds and their extended half-lives in soil. The persistence of systemic pesticides in soil would subsequently render unintended ecological hazards to those nontarget but essential organisms in soil and watersheds. , …”
Section: Introductionmentioning
confidence: 99%
“…The persistence of systemic pesticides in soil would subsequently render unintended ecological hazards to those nontarget but essential organisms in soil and watersheds. 10,11 Earthworms are one of the most important beneficial invertebrate animals in soil biota, contributing 60%−80% of the total animal biomass in healthy soil. Therefore, earthworms have been used as an indicating organism for assessing the health status of soil, or the eco-toxicological impacts resulting from soil contaminations.…”
Section: ■ Introductionmentioning
confidence: 99%